Analysis of the Role of Internal Audit Implementation in Improving the Quality of Financial Statements Sumedang Regency Government (Case Studies on Sumedang Regency Government) - Andi Ahmad Nugroho; Maman Nurachman (LPPM Universitas Sebelas April, 2023)
This study aims to determine how the implementation of internal audit in improving the quality of financial statements of the Sumedang Regency Government. The object of this study is the Sumedang Regency Inspectorate, the method used in this study is a qualitative descriptive method, which is research that is included in the type of qualitative research. Research is expected to reveal facts, circumstances, phenomena, variables and circumstances that occur when the research runs and present what it is. The results of the research obtained show that the implementation of the Financial Statement Audit by the Inspectorate has been carried out well. The conclusion of this study is the preparation of Financial Statements based on the implementation of Financial Statement audits by the Inspectorate in accordance with applicable provisions and procedures